Electro-mechanical response to the harmonic actuation of the pneumatically coupled dielectric elastomer based actuators with and without load. (April 2017) - Sasikala, S.; Madhavan, K.T.; Ramesh, G.; Saggar, S.; Predeep, P.; Chowdhury, P.
Highlights: Electro-mechanical response of the Pneumatically Coupled Dielectric Elastomer (PCDE) based actuators was investigated. High voltage performances of PCDE actuators up to 3kV in the frequency range of 0 to 2 kHz were studied. Harmonics and super harmonic modes were characterized for the time using indigenously developed magnetoresistive field sensor. The phase shift of 180 degree at resonance was observed for PCDE actuators. The actuator have potential applications in Micro aerial Vehicle. Abstract: Pneumatically Coupled Dielectric Elastomer (PCDE) based actuators with air as an intervening medium, were developed. Fabrication of these actuators have been carried out using dielectric elastomer membrane on both sides of an insulating annular holder of diameter 10 mm. The membrane at the bottom side acts as an active membrane which consists of ultrathin metal electrode on it's both sides, whereas top membrane acts as a passive membrane. Mechanical performance of PCDE actuators were studied using bulge test method. Initially, high voltage performance of both active and passive membranes with electric field strength upto 40 MV/m were characterized by sweeping the frequency from 0 to 2 kHz and their frequencies responses were analyzed. With fixing a cylindrical magnet as a load at the center of the passive membrane, further experimental studies on several harmonics along with their phase shift were performed using an indigenously developed magnetoresistive sensor and the detailed analysis on these observations are presented.